Hydrothermal Synthesis of Biphasic Calcium Phosphate from Cuttlebone Assisted by the Biosurfactant L-rhamnose Monohydrate for Biomedical Materials - Thamonwan Tattanon; Premjit Arpornmaeklong; Sarute Ummartyotin; Thirawudh Pongprayoon (ChemEngineering, 2021)
The motivation of this research work is to develop novel medical material from cuttlebone (calcium source) by L-rhamnose monohydrate (biosurfactant) for aged people. The process can be synthesized biphasic calcium phosphate which is eco-friendly to environment. One of the most important aspects for this work is to use cuttlebone as a naturally occurring calcium source from a local beach in Thailand. It usually contains 90% calcium carbonate. The objective of this research work is to synthesize the biphasic calcium phosphate by hydrothermal reaction. Critical micelle concentrations (CMCs) of 10, 20, 100, 500 and 1000 of L-rhamnose monohydrate were used to control particle size and shape. XRD revealed a mixture of β-tricalcium phosphate and hydroxyapatite powder. SEM reported that the size of particles can be effectively controlled by the addition of L-rhamnose monohydrate, and with the addition of surfactant, size uniformity was achieved. The cytotoxicity test was reported to be in the range of 70–75%. It was remarkable to note that biphasic calcium phosphate synthesized from cuttlebone with the aid of L-rhamnose monohydrate will be considered an excellent candidate as a scaffold material.